Suicidal behaviour in adolescence and later mental healthcare use: a population-based registry study of Norwegian youth. Exploring potential gender differences and ethnic differences between indigenous Sami and non-Sami - Sørvold, Maria Therene (UiT Norges arktiske universitet, 2017)
Background: The prevalence of suicidal behaviour among adolescents are high, and act as a risk factor of suicide. Suicide is considered a public health problem worldwide. Indigenous people are in general at higher risk of suicide than the majority population, and there are gender differences in the pathways of suicidal behaviour and suicides. Objectives: To investigate the association and importance of suicidal behaviour in northern Norwegian adolescents and the use of mental healthcare in young adulthood, and to explore potential gender differences and differences between the indigenous Sami and non-Sami. Material and method: 3987 (68%) of all 10th grade students in northern Norway participated in the Norwegian Arctic Adolescents Health Study (NAAHS) in 2003-2005. Suicidal thoughts, suicidal attempts and self-harm was measured in the NAAHS at the age of 15-16 years. NAAHS and was linked to the Norwegian Patient Registry in the years of 2008-2012. Pearson Chi-Square test and one-way ANOVA was used for the univariate analyses, and hierarchical binary logistic regression was used for the multivariable analyses. Separate logistic regression analyses were made for the three suicidal behaviours. Results: Suicidal thoughts, suicide attempts and self-harm in adolescence significantly increased the use of mental healthcare in young adulthood. Females had more suicidal behaviour and a higher mental healthcare use than males, however gender was not a significant predictor of the use of mental healthcare. The indigenous Sami reported more suicidal thoughts, but ethnicity was not a significant predictor for the use of mental healthcare. Conclusion: Many adolescents have suicidal behaviour, however, most of them are not in need of mental healthcare in young adulthood. The indigenous Sami were not worse off than the non-Sami, and have less suicidal behaviour than other indigenous populations. This is important in a global health perspective, for other indigenous populations.